2009
DOI: 10.1128/jb.00502-09
|View full text |Cite
|
Sign up to set email alerts
|

Directed Evolution of Ionizing Radiation Resistance in Escherichia coli

Abstract: We have generated extreme ionizing radiation resistance in a relatively sensitive bacterial species, Escherichia coli, by directed evolution. Four populations of Escherichia coli K-12 were derived independently from strain MG1655, with each specifically adapted to survive exposure to high doses of ionizing radiation. D 37 values for strains isolated from two of the populations approached that exhibited by Deinococcus radiodurans. Complete genomic sequencing was carried out on nine purified strains derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
150
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(158 citation statements)
references
References 60 publications
7
150
1
Order By: Relevance
“…Diaz and Schulze-Makuch (141) showed that D. radiodurans could survive Martian-like conditions of low temperatures (ÏȘ35°C for 10 days), low pressure (83.3 kPa for 10 days), and high UV radiation (37 W/m 2 for 24 h), which occur near the surface of Mars. The "training" of radiation resistance was demonstrated experimentally on different bacteria (E. coli, Bacillus pumilus, and Salmonella enterica serovar Typhimurium) exposed to multiple cycles of high radiation doses that yielded a permanently acquired increase in radiation resistance (132,238,358,481).…”
Section: Ionizing Radiation Resistance Of D Radioduransmentioning
confidence: 99%
“…Diaz and Schulze-Makuch (141) showed that D. radiodurans could survive Martian-like conditions of low temperatures (ÏȘ35°C for 10 days), low pressure (83.3 kPa for 10 days), and high UV radiation (37 W/m 2 for 24 h), which occur near the surface of Mars. The "training" of radiation resistance was demonstrated experimentally on different bacteria (E. coli, Bacillus pumilus, and Salmonella enterica serovar Typhimurium) exposed to multiple cycles of high radiation doses that yielded a permanently acquired increase in radiation resistance (132,238,358,481).…”
Section: Ionizing Radiation Resistance Of D Radioduransmentioning
confidence: 99%
“…Experimental evolution studies combined with genome resequencing have correlated specific mutations to phenotypic changes to demonstrate that these dynamic genome reorganizational events are tightly coupled to adaptive evolution (Herring et al 2006;Barrick et al 2009). Interestingly, several studies have reported that, along with metabolic and structural genes, mutations within regulatory genes are also adaptive (Harris et al 2009;Wang et al 2010), which suggests that altering gene regulatory programs is an effective strategy for adaptation over short time intervals. Despite benefits of efficient coordinate regulation due to operonization, there is a surprisingly low level of conservation in operon structures across organisms.…”
mentioning
confidence: 99%
“…To explore the existence and nature of such putative protective mechanisms, we quantitatively examined oxidation (carbonylation) of the proteomes of sensitive and resistant strains of D. radiodurans and E. coli (including two radiation-resistant variants of E. coli evolved experimentally by exposure of surviving cells to successively increasing doses of ionizing radiation (20 cycles) (7). We show here that killing of D. radiodurans and E. coli strongly correlates with proteome carbonylation (PC) and that this correlation is independent of the extent of cellular resistance or the type of lethal agent used.…”
mentioning
confidence: 99%